2020
DOI: 10.1111/nph.16649
|View full text |Cite
|
Sign up to set email alerts
|

Drought‐induced lacuna formation in the stem causes hydraulic conductance to decline before xylem embolism in Selaginella

Abstract: Summary Lycophytes are the earliest diverging extant lineage of vascular plants, sister to all other vascular plants. Given that most species are adapted to ever‐wet environments, it has been hypothesized that lycophytes, and by extension the common ancestor of all vascular plants, have few adaptations to drought. We investigated the responses to drought of key fitness‐related traits such as stomatal regulation, shoot hydraulic conductance (Kshoot) and stem xylem embolism resistance in Selaginella haematodes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 88 publications
(106 reference statements)
0
16
1
Order By: Relevance
“…The extent of the lacunae remained unchanged for 12 h of dehydration (42.9% ±19.9 sd ), and increased to 55.6% (±7.1 sd ) after 24 h of dehydration, that is, over half of the stele separated from the surrounding cortex as the stipes dehydrated. Unlike in Selaginella ( Cardoso et al, 2020 ), we did not observe any trabeculae, endodermal cells that connect the cortex with the pericycle and the vasculature. Lacunae quickly disappeared as the pericycle and endodermis swelled to meet the cortex cells during the rehydration ( Figures 3 and 4 ).…”
Section: Resultscontrasting
confidence: 99%
“…The extent of the lacunae remained unchanged for 12 h of dehydration (42.9% ±19.9 sd ), and increased to 55.6% (±7.1 sd ) after 24 h of dehydration, that is, over half of the stele separated from the surrounding cortex as the stipes dehydrated. Unlike in Selaginella ( Cardoso et al, 2020 ), we did not observe any trabeculae, endodermal cells that connect the cortex with the pericycle and the vasculature. Lacunae quickly disappeared as the pericycle and endodermis swelled to meet the cortex cells during the rehydration ( Figures 3 and 4 ).…”
Section: Resultscontrasting
confidence: 99%
“…Recent studies have shown that the vascular strand pulls away from the surrounding parenchyma during later stages of dehydration, such that lacunae surround the phloem tissue (Holmlund et al ., 2019; Cardoso et al ., 2020), while the xylem remains functional (Cardoso et al ., 2020). It is conceivable that the phloem functions in a protective role to maintain hydraulic continuity in the xylem, which may otherwise be vulnerable to air‐seeding.…”
Section: Discussionmentioning
confidence: 99%
“…Although increasing levels of foliar ABA has long been associated with stomatal closure and increases in WUE in angiosperm species during drought [1,38,67,70,71], it has recently been discovered that the stomata of ferns and lycophytes do not close in response to both endogenous and exogenous ABA [72][73][74]. Instead, in these early-diverging species, changes in leaf water status regulate stomatal aperture by an ABA-independent, hydropassive mechanism [72,75,76].…”
Section: Linking Aba With Stomatal Aperture and Xylem Embolismmentioning
confidence: 99%